Handbook of child and adolescent drug and substance abuse : pharmacological, developmental, and clinical considerations - Pagliaro, Louis A.; Pagliaro, Ann M. (John Wiley and Sons, 2012)
More than 90 percent of adults with current substance use disorders started using before age 18, engaging in behaviors that affect healthy neurological and psychological development. This handbook provides a comprehensive, up-to-date overview of the nature and extent of substance use by children and adolescents